Blood donation trends in Zhejiang Province, 2017–2025: an ecological study before, during, and after COVID-19 - Guihua Jiang; Yani Ye; Hongyun Wang; Jinhui Wu; Jinhui Liu; Jun Xu (Frontiers in Public Health, 2026)
Background Voluntary blood donation is fundamental to ensuring a safe and adequate blood supply for clinical transfusion. The COVID-19 pandemic posed unprecedented challenges to global blood collection systems, including those in China. This ecological study aimed to characterize long-term blood donation patterns in Zhejiang Province from 2017 to 2025, spanning the pre-pandemic, pandemic, and post-pandemic periods. Methods The blood donation data from 2017 to 2025 were obtained from the BIS 3.0 database maintained by the Blood Center of Zhejiang Province. These data included the number of donations, donated volume, donor demographics, as well as blood supply volume. A descriptive ecological design was employed for analysis. Results The blood donation rate per 1,000 population, the total number of blood donations, and whole blood donation indicators exhibited an upward trend from 2020 to 2022, followed by a decline in the post-pandemic period. The male-to-female donor ratio (≈3:2) remained stable. The proportion of young donors (18≤ to <25 years) declined by 46.2%. Conversely, donors aged 55≤ to <60 years increased from 1 to 3%, representing the largest relative growth among all age groups. Among occupational groups, the proportions of employees, medical staff, and workers returned to earlier levels after the pandemic, whereas the proportion of students recovered more slowly. The supply of red blood cells and plasma declined after 2022, while platelet supply continued to increase. Conclusion These results reveal marked shifts in blood donation dynamics temporally associated with the pandemic and its aftermath. Therefore, targeted incentives, public awareness, and trend monitoring are warranted to enhance the resilience of the blood supply system.